Chest trauma clinical practice guideline protects against delirium in patients with rib fractures - Valérie Courval; Raymond Tang; Peter Rose; Naisan Garraway; Robin Som; Jenna Kroeker; Anas Wess; Yuwei Yang; Bader Al-Zeer; Harjot Uppal; Patricia Balmes; Nasira Lakha; et al. (Trauma Surgery & Acute Care Open)
Introduction Traumatic rib fractures present a considerable risk to patient well-being, contributing to morbidity and mortality in trauma patients. To address the risks associated with rib fractures, evidence-based interventions have been implemented, including effective pain management, pulmonary hygiene, and early walking. Vancouver General Hospital, a level 1 trauma center in British Columbia, Canada, developed a comprehensive multidisciplinary chest trauma clinical practice guideline (CTCPG) to optimize the management of patients with rib fractures. This prospective cohort study aimed to assess the impact of the CTCPG on pain management interventions and patient outcomes.Methods The study involved patients admitted between January 1, 2021 and December 31, 2021 (post-CTCPG cohort) and a historical control group admitted between November 1, 2018 and December 31, 2019 (pre-CTCPG cohort). Patient data were collected from patient charts and the British Columbia Trauma Registry, including demographics, injury characteristics, pain management interventions, and relevant outcomes.Results Implementation of the CTCPG resulted in an increased use of multimodal pain therapy (99.4% vs 96.1%; p=0.03) and a significant reduction in the incidence of delirium in the post-CTCPG cohort (OR 0.43, 95% CI 0.21 to 0.80, p=0.0099). There were no significant differences in hospital length of stay, ICU (intensive care unit) days, non-invasive positive pressure ventilation requirement, ventilator days, pneumonia incidence, or mortality between the two cohorts.Discussion Adoption of a CTCPG improved chest trauma management by enhancing pain management and reducing the incidence of delirium. Further research, including multicenter studies, is warranted to validate these findings and explore additional potential benefits of the CTCPG in the management of chest trauma patients.Level of evidence IIb.